2012
DOI: 10.1016/j.jacc.2011.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Translational Studies of Lipoprotein-Associated Phospholipase A2 in Inflammation and Atherosclerosis

Abstract: Objectives To examine the role of lipoprotein-associated phospholipase A2 (Lp-PLA2/PLA2G7) in human inflammation and coronary atherosclerosis. Background Lp-PLA2 has emerged as a potential therapeutic target in coronary heart disease (CHD). Data supporting Lp-PLA2 are indirect and confounded by species differences; whether Lp-PLA2 is causal in CHD remains in question. Methods We examined inflammatory regulation of Lp-PLA2 during experimental endotoxemia in human, probed the source of Lp-PLA2 in human leuko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 47 publications
3
42
0
3
Order By: Relevance
“…This expression pattern was seen on both dyslipidemia and type II diabetes mellitus condition. This study supports a previous scientific proof (in vitro study) that found Lp-PLA 2 formation is dramatically increased in an arterial blood vessel at the time of monocyte differentiation into macrophage which occurs in a much early (Cao et al, 1998;Ferguson et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This expression pattern was seen on both dyslipidemia and type II diabetes mellitus condition. This study supports a previous scientific proof (in vitro study) that found Lp-PLA 2 formation is dramatically increased in an arterial blood vessel at the time of monocyte differentiation into macrophage which occurs in a much early (Cao et al, 1998;Ferguson et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…mRNA Lp-PLA 2 expression pattern is significantly increased in 16 weeks experimental groups (both dyslipidemia and type II diabetes mellitus conditions). This findings support previous an in vitro study findings which found that the early phase of inflammation process (monocyte to macrophage pre-transformation phase), mRNA Lp-PLA 2 expression level are so low to be detected in the blood, mRNA Lp-PLA 2 expression will significantly increase in blood after macrophage maturation phase (longer observation period phase) (Ferguson et al, 2012). Even though there is a possibility that Lp-PLA 2 is produced by macrophage locally in aortic tissue can also contribute to half of circulating Lp-PLA 2 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Monocyte/macrophages are key players in both initiation and progression of atherosclerosis, and they have been proposed as new potential therapeutic targets for the prevention and treatment of this disease ( 42 ). We previously demonstrated that maturation of monocytes into macrophages is accompanied by dramatic increases in Lp-PLA 2 mRNA and protein ( 21,43 ); these observations were recently confi rmed ( 44 ). Treatment of macrophages with acetylated LDL generates foam cells in vitro and further increases Lp-PLA 2 expression ( 44 ), which is consistent with observations in human atherosclerotic plaques ( 45 ).…”
Section: Cellular Sources and Regulation Of Expressionmentioning
confidence: 89%